Crescimento de Plectranthus barbatus Andr. sob estresse hídrico - Silva, Hellen Lilian Matos da (2021)
The water stress is one of the main factors that alter the plant metabolism and affects its development. In order to verify the effects of water stress on the growth of the species Plectranthus barbatus Andrews, seedlings were grown in 7.35 L pots containing manure plus soil and submitted to water restriction for 1 day, 2 days, 3 days, 4 days, and 5 days. The plants were collected at 90 days after the beginning of the treatments and the fresh biomass was weighed, and one treatment was taken as sample to obtain dry mass by drying in a forced circulation oven at 65ºC. The thermal requirement of the crop was 3253 °C per day for the evaluation period, which was within the ideal. The plants with a smaller water replacement interval, 2 days, presented a ky of 0.92. The plants irrigated every 5 days showed a ky equal to 2, indicating greater sensitivity to the deficit. The water deficit caused reductions in leaf expansion, number of leaves, height and production of biomass of the aerial part and root. The physiological parameters evaluated through leaf gas exchange analysis, water use efficiency and transpiration of P. barbatus Andrews were also reduced as the dry period increased, as well as the relative water content at the point of turgescence loss (TRA %). The osmotic potential at full turgidity (Ψπ100), the osmotic potential at initial turgidity (Ψπ0) and the water potential (Ψw), although reduced, remained in balance in order to maintain the turgor of the plant through the accumulation of solutes. The cell wall showed greater rigidity or greater volumetric modulus of elasticity (ε) at irrigation intervals 1, 2, 3 and 4. Water restriction reduces Plectranthus barbatus Andrews growth, leaf area leaf area expansion, gas exchange, and photosynthetic rates.